Queen of the Virgins : pageantry and black womanhood in the Caribbean - Oliver, M. Cynthia (Caribbean studies series (Jackson, Miss.), 2009)
Beauty pageants are wildly popular in the U.S. Virgin Islands, outnumbering any other single performance event and capturing the attention of the local people from toddlers to seniors. Local beauty contests provide women opportunities to demonstrate talent, style, the values of black womanhood, and the territory's social mores. Queen of the Virgins: Pageantry and Black Womanhood in the Caribbean is a comprehensive look at the centuries-old tradition of these expressions in the Virgin Islands. M. Cynthia Oliver maps the trajectory of pageantry from its colonial precursors at tea meetings, dance.